Impurity distributions in a magnesium sublimates - Papirov, I.I.; Kravchenko, А.I.; Mazin, А.I.; Shiyan, A.V.; Virich, V.D. (Вопросы атомной науки и техники, 2016)
The dependence of character of impurities distributions in thickness of vacuum sublimation magnesium condensate from its purity is ascertained. The condensate with summary impurities concentration ~ 10⁻³ mas.% has more uniform impurities distribution and bigger part of impurities with monotonic distribution than the condensate with summary impurities concentration ~ 10⁻² mas.%. The impurity concentrations on the surface of rest exceed the impurity concentration inside the rest on moving off 2·μm from surface in 2-600 times (at initial summary impurity concentration ~ 10⁻¹ mas.%). Встановлена залежність характеру розподілу домішок по товщині у конденсаті магнію, що одержано вакуумною сублімацією, від чистоти конденсату. Конденсат з сумарним вмістом домішок ~ 10⁻³ мас.% має більш рівномірний розподіл домішок та більше число домішок с монотонним розподілом, ніж менш чистий конденсат з сумарним вмістом домішок ~ 10⁻² мас.%. Вміст домішок на поверхні залишку в 2-600 раз перевищує вміст домішок всередині залишку на відстані від поверхні > 2 мкм (при вихідному сумарному вмісту ~ 10⁻¹ мас.%). Установлена зависимость характера распределения примесей по толщине конденсата магния, полученного вакуумной сублимацией, от чистоты конденсата. Конденсат с суммарным содержанием примесей ~ 10⁻³ мас.% имеет более равномерное распределение примесей и большее число примесей с монотонным распределением, нежели менее чистый конденсат с суммарным содержанием примесей ~ 10⁻² мас.%. Содержание примесей на поверхности остатка в 2-600 раз превышает исходное содержание примесей внутри остатка на удалении от поверхности более 2 мкм (при исходном суммарном содержании ~ 10⁻¹ мас.%).